2009
DOI: 10.1002/pola.23371
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of novel resorcinarene‐centered amphiphilic star‐block copolymers consisting of eight ABA triblock arms by combination of ROP, ATRP, and click chemistry

Abstract: Novel amphiphilic eight‐arm star triblock copolymers, star poly(ε‐caprolactone)‐block‐poly(acrylic acid)‐block‐poly(ε‐caprolactone)s (SPCL‐PAA‐PCL) with resorcinarene as core moiety were prepared by combination of ROP, ATRP, and “click” reaction strategy. First, the hydroxyl end groups of the predefined eight‐arm SPCLs synthesized by ROP were converted to 2‐bromoesters which permitted ATRP of tert‐butyl acrylate (tBA) to form star diblock copolymers: SPCL‐PtBA. Next, the bromide end groups of SPCL‐PtBA were qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 66 publications
0
34
0
Order By: Relevance
“…These ABA star-triblock copolymers were prepared by a combination of ROP, ATRP, and click chemistry. 105 Unfortunately, contrary to the authors' expectations, self-assembly of this triblock copolymer star in aqueous solution did not lead to any unique new morphology but spherical micelles.…”
Section: Chemical Reviewsmentioning
confidence: 70%
“…These ABA star-triblock copolymers were prepared by a combination of ROP, ATRP, and click chemistry. 105 Unfortunately, contrary to the authors' expectations, self-assembly of this triblock copolymer star in aqueous solution did not lead to any unique new morphology but spherical micelles.…”
Section: Chemical Reviewsmentioning
confidence: 70%
“…Previously, the micelles based on diblock copolymers combining PCL and PAA were stabilized by cross‐linking PAA shell, and then PCL core was selectively degraded to generate nanoscale cage‐like membranes . In other case the amphiphilic eight‐arm star triblock copolymers with PCL‐ b ‐PAA‐ b ‐PCL arms and resorcinarene core were self‐assembled into spherical micelles . However, up to now the studies on PCL/P(M)AA micelles used for drug loading and release have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Amphiphilic polymers have attracted considerable interests in past decades for their unique phase behavior in aqueous medium and potential applications as carriers for genes and hydrophobic drugs 11–14. Poly(ε‐caprolactone) (PCL), a Food and Drug Administration (FDA) approved polyester, has been widely used as the hydrophobic segment in amphiphilic polymers as synthetic biomaterial or controlled drug release matrix 15–24. However, using PCL as backbone to prepare amphiphilic graft polymer is difficult because of the lack of functional groups on PCL chain.…”
Section: Introductionmentioning
confidence: 99%